Implementation of Risk Management at Balai Jasa Konstruksi Wilayah VI Makassar: An ISO 31000:2018 Perspective - Kusumardani, Arifah; Syamsuddin, Syamsuddin (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study examines the implementation of risk management at Balai Jasa Konstruksi Wilayah VI Makassar (BJKW VI Makassar), a public sector agency under the Ministry of Public Works, using the ISO 31000:2018 framework. The research employs a qualitative case study approach to analyze the patterns of risk management implementation, identify key success factors, explore challenges, and evaluate the impact on organizational performance. Data were collected through semi-structured interviews, direct observations, and document analysis involving key stakeholders. The findings show that BJKW VI Makassar has adopted risk management practices in line with ISO 31000:2018 principles, including risk identification, assessment, treatment, and monitoring. Key success factors include strong leadership commitment, adequate resources, effective communication, and a supportive organizational structure. However, challenges such as employee resistance, limited risk-awareness culture, and procedural gaps persist. The study concludes that while the implementation of risk management has led to improvements in operational efficiency and enhanced stakeholder trust, further efforts are needed. These efforts should focus on cultivating a robust risk-aware culture across all organizational levels, updating outdated standard operating procedures, and improving human resource competency to enable more effective risk management. This study contributes to the understanding of ISO 31000:2018’s application in the public sector and offers practical insights for improving risk management practices in similar organizations.